From devil's advocate to crime fighter: confirmation bias and debiasing techniques in prosecutorial decision-making. Issue 5 (28th May 2019) - Lidén, Moa; Gräns, Minna; Juslin, Peter
ABSTRACT: This research examines the role of confirmation bias in prosecutorial decisions before, during and after the prosecution. It also evaluates whether confirmation bias is reduced by changing the decision maker between arrest and prosecution. In Experiment 1, Swedish prosecutors ( N  = 40) assessed 8 scenarios where they either decided themselves or were informed about a colleague's decision to arrest or not arrest a suspect. Participants then rated how trustworthy the suspect's statement was as well as the strength of new ambiguous evidence and the total evidence. They also decided whether to prosecute and what additional investigative measures to undertake. In Experiment 2 the same method was used with Law and Psychology students ( N  = 60). Overall, prosecutors' assessments before the prosecution indicated that they were able to act as their own devil's advocate. Also, their assessments while deciding about whether to prosecute were reasonably balanced. However, after pressing charges, they displayed a more guilt-confirming mindset, suggesting they then took on the role as crime fighters. This differed from the student sample in which higher levels of guilt confirmation was displayed in relation to arrested suspects consistently before, during and after a prosecution decision. The role of prosecutors' working experience is discussed.